Learning Deficits and Attenuated Adaptive Stress Response After Early-Life Seizures in Zebrafish - Singh, Harsimran; Ramon, Alfonsina; Finore, Dana; Burnham, Kaleigh; McRobert, Scott; Lippman-Bell, Jocelyn (Frontiers in Neuroscience, 2022)
Early-life seizures (ELS) are often associated with the development of cognitive deficits. However, methods to predict and prevent these deficits are lacking. To increase the range of research models available to study cognitive consequences of ELS, we investigated whether seizures in larval zebrafish (Danio rerio) lead to behavioral deficits later in life. We thus modified the existing pentylenetetrazole (PTZ)-induced seizure model in larval zebrafish, exposing zebrafish to PTZ daily from 5-7 days post-fertilization (dpf). We then compared later-life learning, social behavior (shoaling), and behavioral and chemical measures of anxiety in the PTZ-exposed zebrafish (PTZ group) to that of naïve clutchmates (untouched controls, UC) and to a second control group (handling control, HC) that experienced the same handling as the PTZ group, but without PTZ exposure. We observed that only the PTZ group displayed a significant deficit in a y-maze learning task, while only the HC group displayed a social deficit of decreased shoaling. HC fish also showed an increased frequency of behavioral freezing and elevated cortisol responses to netting, heightened stress responses not seen in the PTZ fish. Since mild stressors, such as the handling the HC fish experienced, can lead to learned, advantageous responses to stress later in life, we tested escape response in the HC fish, using an acoustic startle stimulus. The HC group showed an enhanced startle response, swimming significantly farther than either the PTZ or UC group immediately after being startled. Taken together, these results indicate that seizures in larval zebrafish impair learning, as well as the development of an adaptive, heightened stress response after early-life stress. These findings expand the behavioral characterization of the larval zebrafish seizure model, strengthening the power of this model for ELS research.